Role of river stage in characterization of phreatic line - Kumar V.; Granthi S. (My University, 2025)
Purpose: The purpose of this study is to understand the basics of interactions of groundwater and surface water, which is needed for effective management of water resources. Design/methodology/approach: The experimental setup was framed using curved flume and the straight flume, which simulates the model of river and groundwater storage, respectively. The model set up further consists, downstream, central and upstream sections where 14 observation wells, which are arranged at a measured distance from the canal side. Findings: Exit gradient is higher at downstream when the average head differences between canal and river are 31.9 cm and 35.7 cm. Free seepage height is more in the downstream wells than upstream and central wells. At the downstream section, there is a greater chance of instability of the riverbank. Research limitations/implications: Results will be used for better planning of hydraulic structural design. Practical implications: Results will help in storing the large water and better irrigation planning for the water acute states and locations. Originality/value: The originality is own developed physical model and its own first type to understand the basic of interaction and effects. © 2020, Emerald Publishing Limited.